MicroRNA-138 promotes acquired alkylator resistance in glioblastoma by targeting the Bcl-2-interacting mediator BIM - Stojcheva, Nina; Schechtmann, Gennadi; Sass, Steffen; Roth, Patrick; Florea, Ana-Maria; Stefanski, Anja; Stuehler, Kai; Wolter, Marietta; Mueller, Nikola S.; Theis, Fabian J.; Weller, Michael; Reifenberger, Guido; et al. (Oncotarget, 2016)
Glioblastoma is the most aggressive brain tumor in adults with a median survival below 12 months in population-based studies. The main reason for tumor recurrence and progression is constitutive or acquired resistance to the standard of care of surgical resection followed by radiotherapy with concomitant and adjuvant temozolomide (TMZ/RT→TMZ). Here, we investigated the role of microRNA (miRNA) alterations as mediators of alkylator resistance in glioblastoma cells. Using microarray-based miRNA expression profiling of parental and TMZ-resistant cultures of three human glioma cell lines, we identified a set of differentially expressed miRNA candidates. From these, we selected miR-138 for further functional analyses as this miRNA was not only upregulated in TMZ-resistant versus parental cells, but also showed increased expression in vivo in recurrent glioblastoma tissue samples after TMZ/RT→TMZ treatment. Transient transfection of miR-138 mimics in glioma cells with low basal miR-138 expression increased glioma cell proliferation. Moreover, miR-138 overexpression increased TMZ resistance in long-term glioblastoma cell lines and glioma initiating cell cultures. The apoptosis regulator BIM was identified as a direct target of miR-138, and its silencing mediated the induced TMZ resistance phenotype. Altered sensitivity to apoptosis played only a minor role in this resistance mechanism. Instead, we identified the induction of autophagy to be regulated downstream of the miR-138/BIM axis and to promote cell survival following TMZ exposure. Our data thus define miR-138 as a glioblastoma cell survival-promoting miRNA associated with resistance to TMZ therapy in vitro and with tumor progression in vivo.
CRIS-Team Scopus Importer:2023-03-08
Keywords: BIM; chemoresistance; Glioblastoma; miR-138; Temozolomide